2016
DOI: 10.1097/qad.0000000000001076
|View full text |Cite
|
Sign up to set email alerts
|

Improvements over time in short-term mortality following myocardial infarction in HIV-positive individuals

Abstract: OBJECTIVE Few studies have described mortality and clinical outcomes after myocardial infarction (MI) in the HIV-positive population. This study evaluated changes in short-term mortality after MI in HIV-positive individuals in the D:A:D Study, and investigated possible reasons for any changes seen. DESIGN Prospective cohort study. METHODS Demographic, cardiovascular disease (CVD)/HIVrelated characteristics and CVD-related interventions (invasive cardiovascular procedures and drug interventions) were summarized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…12 The proportionate mortality from CVD has also significantly increased in HIV over time; from 1999 to 2013, overall mortality increased but CVD mortality increased. 13 Yet recent data suggest that absolute rates of myocardial infarction (MI) among HIV-infected individuals are decreasing over time, 14 an advance thought to reflect improvement in recognition and management of CVD risk factors.…”
Section: The Impact Of Hiv On Ischemic Heart Diseasementioning
confidence: 99%
“…12 The proportionate mortality from CVD has also significantly increased in HIV over time; from 1999 to 2013, overall mortality increased but CVD mortality increased. 13 Yet recent data suggest that absolute rates of myocardial infarction (MI) among HIV-infected individuals are decreasing over time, 14 an advance thought to reflect improvement in recognition and management of CVD risk factors.…”
Section: The Impact Of Hiv On Ischemic Heart Diseasementioning
confidence: 99%
“…In the DAD study, the observed decrease in CVD-related deaths over time could not be explained by the higher proportion of virologically suppressed individuals, suggesting that deployment of primary prevention measures such as smoking cessation, prescription of lipid-lowering drugs, diet and exercise modifications may be responsible [2]. This hypothesis was supported by a recent study that assessed the short-term mortality after MI in the same cohort [6]. It confirmed that prescription of lipid-lowering drugs and anti-platelet agents resulted in significantly improved survival rates, despite the older age and poorer CVD risk profile of in individuals who experienced an MI.…”
Section: Traditional Risk Factorsmentioning
confidence: 79%
“…There has been recent interest in recurrence of and morbidity and mortality after myocardial infarction. Data from the Data Collection on Adverse Drug Events (D:A:D) study indicates that the proportion of PLWHA dying from a CVD cause after their initial myocardial infarction decreased from 73% in 1999–2002 to 41% in 2011–2014 [59]. They conclude that short-term survival improvements following a myocardial infarction are primarily due to better management of CVD risk factors in PLWHA who have an incident myocardial infarction.…”
Section: Myocardial Infarctionmentioning
confidence: 99%